A PORTRAIT OF INNOVATION IN ARABIC LANGUAGE LEARNING IN INDONESIAN EDUCATION - Slamet Daroini; Mirdawati Razida; Ali Al Haddad; Arham Ahmad (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Arabic language learning in Indonesia has experienced significant developments along with changing times and technological advances. Initially dominated by traditional methods such as sorogan and bandongan, now Arabic language learning has begun to adopt a more innovative, communicative, and contextual approach. This study aims to describe a portrait of innovation in Arabic language learning at various levels of education in Indonesia through a literature review and qualitative descriptive approach. The results of the study show that teaching materials are now more diverse, including textbooks, digital media, and AI-based applications. In addition, various learning methods, such as Thariqah al-Qawā‘id wa at-Tarjamah, Thariqah al-Mubāsyarah, Thariqah al-Ilhīyah, used to adjust learning to the needs of students. This innovation encourages the creation of a more active, relevant, and meaningful learning process. Thus, the development of Arabic language learning must continue to be directed at an adaptive approach to the dynamics of the times and the character of students.